Acute parotitis due to MRSA causing Lemierre's syndrome. Issue 5 (31st May 2018) - Alabraba, Edward; Manu, Nichola; Fairclough, Gemma; Sutton, Robert
Abstract: We report a case of septic thrombophlebitis of the right internal jugular vein linked with right-sided acute parotitis caused by methicillin-resistant Staphylococcus aureus (MRSA) in a patient who had recently undergone a pylorus-preserving pancreaticoduodenectomy. Our case is unique because acute parotitis is a less-recognized cause of Lemierre's syndrome, never previously linked with MRSA infection in this context. We review the literature on diagnosis and management of Lemierre's syndrome caused by acute parotitis. Prompt diagnosis and aggressive antibiotics ensured a favourable outcome.